Cerebral hypomyelination associated with biallelic variants of FIG4. Issue 5 (28th February 2019) - Lenk, Guy M.; Berry, Ian R.; Stutterd, Chloe A.; Blyth, Moira; Green, Lydia; Vadlamani, Gayatri; Warren, Daniel; Craven, Ian; Fanjul‐Fernandez, Miriam; Rodriguez‐Casero, Victoria; Lockhart, Paul J.; Vanderver, Adeline; et al.
Abstract: The lipid phosphatase gene FIG4 is responsible for Yunis‐Varón syndrome and Charcot‐Marie‐Tooth disease Type 4J, a peripheral neuropathy. We now describe four families with FIG4 variants and prominent abnormalities of central nervous system (CNS) white matter (leukoencephalopathy), with onset in early childhood, ranging from severe hypomyelination to mild undermyelination, in addition to peripheral neuropathy. Affected individuals inherited biallelic FIG4 variants from heterozygous parents. Cultured fibroblasts exhibit enlarged vacuoles characteristic of FIG4 dysfunction. Two unrelated families segregate the same G>A variant in the +1 position of intron 21 in the homozygous state in one family and compound heterozygous in the other. This mutation in the splice donor site of exon 21 results in read‐through from exon 20 into intron 20 and truncation of the final 115 C‐terminal amino acids of FIG4, with retention of partial function. The observed CNS white matter disorder in these families is consistent with the myelination defects in the FIG4 null mouse and the known role of FIG4 in oligodendrocyte maturation. The families described here the expanded clinical spectrum of FIG4 deficiency to include leukoencephalopathy.